Disparities in melanoma incidence and mortality in South-Eastern Europe: Increasing incidence and divergent mortality patterns. Is progress around the corner?. (March 2016) - Barbaric, Jelena; Sekerija, Mario; Agius, Dominic; Coza, Daniela; Dimitrova, Nadya; Demetriou, Anna; Safaei Diba, Chakameh; Eser, Sultan; Gavric, Zivana; Primic-Zakelj, Maja; Zivkovic, Snezana; Zvolsky, Miroslav; et al.
Abstract: Introduction: Most countries in South-Eastern Europe (SEE) have lower incidence, but higher mortality rates of malignant melanoma (MM) of the skin compared to North-Western Europe (NWE). We explored trends in MM incidence and mortality in SEE countries by sex and age and compared them with the trends in NWE. Methods: We obtained data on incident cases and deaths from MM (ICD-10 code C43) from 11 population-based cancer registries in Bosnia and Herzegovina, Bulgaria, Croatia, Cyprus, Czech Republic, Malta, Romania, Serbia, Slovakia, Slovenia and Turkey. We calculated age-specific rates for 25–49 ('young'), 50–69 ('middle aged') and 70+ years ('older') and estimated the average annual percent of change in incidence and mortality trends 2000–2010 according to age group and sex, using joinpoint regression analysis. Findings: The incidence rates of MM across the region were uniformly increasing. Significant increases in mortality rates were observed in middle aged men in Serbia and Bulgaria, middle aged women in Slovenia, older men in the Czech Republic, Serbia and Turkey, and older women in Slovenia and Serbia. Interpretation: While MM incidence rates were still increasing across SEE, mortality trends diverged and were less favourable than in NWE. Empowering cancer registration and improving the quality of incidence and mortality data will be essential for monitoring progress in MM control. In the context of prevention of melanoma, disparities in early detection appear to be widening the gap between SEE and NWE, while the provision of care to patients with advanced disease is likely to prove a challenge for regional healthcare budgets. Highlights: Melanoma incidence rates in South-Eastern Europe were uniformly increasing over the 2000–2010 period. Incidence rates were higher in men than in women at middle and older ages in most countries. Trends in mortality rates diverged but were less favourable than in North-Western Europe. Empowering cancer registration in the region will be essential for monitoring progress.